Phosphorus and base cations drive contrasting root dynamics in a central Amazon forest - Jéssica Schmeisk-Rosa; Kelly M. Andersen; Amanda L. Cordeiro; Anna Carolina Martins Moraes; Ana Cláudia Francisco Salomão; Rafael Leandro de Assis; Raffaello Di Ponzio; Renata Vilar de Almeida; Maria Pires Martins; Hellen Fernanda Viana Cunha; Nathielly Pires Martins; Sheila Trierveiler de Souza; et al. (Plant and Soil, 2026)
Background and aims In highly weathered soils of central Amazonia, where nutrients such as phosphorus (P) and base cations are scarce, fertilization experiments have demonstrated above- and belowground effects on total net primary productivity (NPP). This study examined how fine root stocks and turnover responded to added nutrients over a two-year period. We predicted that adding a limiting nutrient would decrease fine root stocks and increase turnover, with the strongest effects from P, followed by base cations, and no response to N. Methods Fine roots (< 2 mm diameter) were sampled from the 0–30 cm soil layer in a low-fertility primary forest in central Amazon subjected to a large-scale factorial experiment adding P, base cations, and N over two years. Fine root turnover was calculated as the ratio between fine root productivity, measured with in-growth cores, and fine root stock. Results Fine root stocks remained unchanged with nutrient addition. However, P increased root turnover by 23% and 48% in the first and second years, respectively, while base cations addition reduced turnover by 24% in year two. N had no significant effect, though a trend toward reduced turnover was observed in the second year. Conclusion The results of this study show that fine root standing stock and turnover in the central Amazon are regulated by soil nutrient availability, especially P and base cations. The contrasting responses observed suggest distinct belowground resource-use strategies for different nutrients, shaped by the nutrient specific mobility in the soil and physiological role in the plant.

Comparing tree swallow dispersal strategies in a continuous mainland environment - Kelly K. Hallinger; Teresa M. Pegan; Michael J. Andersen; Daniel R. Ardia; Amos Belmaker; David Chang van Oordt; Valentina Ferretti; Anna M. Forsman; Jennifer R. Gaul; Paulo E. Llambías; Sophia C. Orzechowski; J. Ryan Shipley; et al. (Ecology, 2026)
Dispersal is one of the most important aspects of animal behavior and can have far‐reaching consequences for organismal ecology and evolution. Despite recent theoretical advances in understanding why individuals within the same population vary in dispersal behavior, relatively few studies have empirically evaluated the long‐term causes and consequences of variable dispersal within natural populations. In this study, we used life history data collected over the course of 16 years to examine fitness outcomes in 867 known‐age female tree swallows breeding in New York, USA, that differed in their dispersal status: “immigrant” females, defined as dispersers that hatched elsewhere, and “local” females, defined as non‐dispersers that hatched within the study site and returned there after migration to breed. We also compared the life history responses of immigrant and local females to natural variation in weather, nest predation risk, and social environment at their breeding site. Local females were more likely to produce fledglings that recruited into the study area as adults. We also found several instances in which dispersal status interacted with an environmental metric to influence relative fitness, and these responses were largely consistent across life history measures. Overall, immigrant females were relatively resilient to variation in their extrinsic environment, while local females were highly sensitive to environmental conditions at the breeding site, performing relatively well when conditions were benign and faring relatively poorly as conditions became more stressful. We found little evidence that distance dispersed within a study site impacted female fitness, suggesting that the dispersal‐associated differences in fitness that we observed operate mostly across broader spatial scales. Future work should undertake the direct and simultaneous measurement of behavior, physiology, and fitness of immigrant and local females across environmental contexts and should seek to understand whether and how context‐dependent fitness variation of dispersers and non‐dispersers scales up to influence larger ecological and evolutionary processes.

Redfield revisited: Insights into freshwater seston carbon : nitrogen : phosphorus stoichiometry - Isabelle M. Andersen; Jason M. Taylor; Daniel Graeber; Patrick T. Kelly; Alexa K. Hoke; Caleb J. Robbins; J. Thad Scott (Limnology and Oceanography, 2025)
Seston carbon (C), nitrogen (N), and phosphorus (P) stoichiometry plays a fundamental role in aquatic ecosystems, influencing nutrient cycling, primary and secondary production, and trophic interactions. In freshwater systems such as lakes, P limitation is more common, whereas in marine environments, N more frequently limits primary production, reflecting different nutrient limitation patterns across aquatic ecosystems. The Redfield ratio (C 106 : N 16 : P 1 molar), developed from marine seston, has long been considered a benchmark for nutrient composition and a predictor of nutrient limitation across aquatic ecosystems. A later global freshwater and marine seston survey proposed the Sterner ratio (C 166 : N 20 : P 1 molar) as a broader global seston average. We present the results of a fully replicated, multi‐annual freshwater mesocosm experiment testing the effect of variable resource N : P stoichiometry on seston stoichiometry. We found that the seston C : N : P ratio aligned with the Redfield ratio under N‐limited conditions, while P‐limited conditions aligned with the Sterner global survey of freshwater ecosystems. Ternary plots offered visual insight into stoichiometric shifts, showing a trend toward P depletion relative to C and N as N : P supply increases. The average seston C : N : P ratio observed from our experimental data was C 141 : N 22 : P 1 (molar) and variation in seston C : N : P was small compared to the resource ratio gradient. Our mesocosm experiment showed that the Redfield ratio provides a useful description of seston stoichiometry in N‐limited freshwater ecosystems. These findings advance the understanding of bottom‐up controls on seston C : N : P stoichiometry and highlight the need to refine ecological theories regarding the application of the Redfield ratio in freshwater ecosystems.

Correction to: Antiretroviral drugs induce oxidative stress and neuronal damage in the central nervous system - Cagla Akay; Michael Cooper; Akinleye Odeleye; Brigid K. Jensen; Michael G. White; Fair Vassoler; Patrick J. Gannon; Joseph Mankowski; Jamie L. Dorsey; Alison M. Buch; Stephanie A. Cross; Denise R. Cook; et al. (Journal of NeuroVirology, 2025)

TropiRoot 1.0: Database of tropical root characteristics across environments - Amanda L. Cordeiro; Daniela F. Cusack; Nathaly Guerrero‐Ramírez; Richard J. Norby; Laura Toro; Michelle Y. Wong; S. Joseph Wright; Kristine Grace M. Cabugao; Kelly M. Andersen; Lucia Fuchslueger; Colleen M. Iversen; Fiona Soper; et al. (Ecology, 2025)
Tropical ecosystems contain the world's largest biodiversity of vascular plants. Yet, our understanding of tropical functional diversity and its contribution to global diversity patterns is constrained by data availability. This discrepancy underscores an urgent need to bridge data gaps by incorporating comprehensive tropical root data into global datasets. Here, we provide a database of tropical root characteristics. This new database, TropiRoot 1.0, will be instrumental in evaluating an array of hypotheses pertaining to root functional ecology and plant biogeography, both within the tropics and relative to other global biomes. The data compilation was conducted by the TropiRoot Initiative, in partnership with the Fine‐Root Ecology Database (FRED) and the Global Root Trait (GRooT) database, Colorado State University (CSU) and the Smithsonian Tropical Research Institute (STRI). Literature search and data extraction were conducted between 2020 and 2024. Literature was identified using Web of Science, Scopus, and complemented using the expert knowledge of members of TropiRoot. To provide broad environmental and geographical distributions, literature searches included root characteristics (traits) across global change drivers, natural gradients, and from different continents. We adopted FRED standardized data columns and streamlined the format to enhance accessibility for data extraction across various user groups. This optimized framework resulted in a smaller, yet comprehensive datasheet. To make the database compatible with other global root trait initiatives, column identification was standardized following the codes provided by FRED. These efforts culminated in data extracted from 104 new sources, resulting in more than 8000 rows of data (either species or community data). Most of the data in TropiRoot 1.0 include root characteristics such as root biomass, morphology, root dynamics, mass fraction, architecture, anatomy, physiology, and root chemistry. This initiative represents a 30% increase in the currently available data for tropical roots in FRED. TropiRoot 1.0 contains root characteristics from 25 different countries, where seven are located in Asia, six in South America, five in Central America and the Caribbean, four in Africa, two in North America, and 1 in Oceania. Due to the volume of data, when ancillary data were available, including soil data, these data were either extracted and included in the database or its availability was recorded in an additional column. Multiple contributors checked the entries for outliers during the collation process to ensure data quality. For text‐based observations, we examined all cells to ensure that their content relates to their specific categories. For numerical observations, we ordered each numerical value from least to greatest and plotted the values, checking apparent outliers against the data in their respective sources and correcting or removing incorrect or impossible values. Some data (soil and aboveground) have different columns for the same variable presented in different units, including originally published units, but root characteristics data had units converted to match those reported in FRED. By filling a gap from global databases, TropiRoot 1.0 expands our knowledge of otherwise so far underrepresented regions and our ability to assess global trends. This advancement can be used to improve tropical forest representation in vegetation models. The data are freely available and should be cited when used.

Increased sea level rise accelerates carbon sequestration in a macro-tidal salt marsh - Rey Harvey Suello; Daan Temmerman; Steven Bouillon; Zeinab Khalifeh; Marinka van Puijenbroek; Kelly Elschot; Ignace Pelckmans; Thorbjørn Joest Andersen; Chris Smit; Jan Bakker; Stijn Temmerman (Science of The Total Environment, 2025)

Nitrogen fixation may not alleviate stoichiometric imbalances that limit primary production in eutrophic lake ecosystems - Isabelle M. Andersen; Jason M. Taylor; Patrick T. Kelly; Alexa K. Hoke; Caleb J. Robbins; J. Thad Scott (Ecology, 2025)
Ecosystem‐scale primary production may be proximately limited by nitrogen (N) but ultimately limited by phosphorus (P) because N 2 fixation contributes new N that accumulates relative to P at ecosystem scales. However, the duration needed to transition between proximate N limitation and ultimate P limitation remains unknown for most ecosystems, including lakes. Here we present the results of a fully replicated, multi‐annual lake mesocosm experiment that permitted full air‐water‐sediment interactions that mimicked lake ecosystem ecology. We manipulated N supply relative to P to achieve a gradient of N:P stoichiometry. Despite N 2 fixation contributing as much as 80% of reactive N in the low N treatments, phytoplankton biomass in these treatments was not different from the unfertilized controls. This suggests that primary production remained N limited in the lowest N treatments, even when N 2 fixation was substantial. Although fixed N inputs reduced the N imbalance relative to P in the low N treatments seasonally, fixed N did not accumulate over multiple years. Additionally, reactive N did not readily accumulate in the high N treatments. Instead, water column stoichiometry was proportional to the experimental N and P additions, suggesting a strong influence from external nutrient loading. Thus, we found no evidence that N accumulation from N 2 fixation was sufficient to trigger a transition to ultimate P limitation seasonally or across our 3‐year experiment. Rather, our results indicate that proximate N limitation perpetuates in eutrophic lakes, likely due to N export being proportional to its inputs. These findings offer new insight regarding the biogeochemical controls on ecosystem stoichiometry and their influence on the timeframe for proximate N limitation and ultimate P limitation in freshwater, marine, and terrestrial ecosystems.

Environmental stressors and zoonoses in the Arctic: Learning from the past to prepare for the future - Emilie Andersen-Ranberg; Ingebjørg H. Nymo; Pikka Jokelainen; Anastasia Emelyanova; Solveig Jore; Brian Laird; Rebecca K. Davidson; Sonja Ostertag; Emilie Bouchard; Freja Fagerholm; Kelly Skinner; Mario Acquarone; et al. (Science of The Total Environment, 2024)

Coefficients in Taylor's law increase with the time scale of water clarity measurements in a global suite of lakes - Max R. Glines; Renata C. H. Amancio; Mikkel René Andersen; Helen Baulch; Ludmila S. Brighenti; Hannah E. Chmiel; Joel E. Cohen; Elvira de Eyto; Oxana Erina; Heidrun Feuchtmayr; Giovanna Flaim; Andrea Giudici; et al. (Ecology Letters, 2024)
Identifying the scaling rules describing ecological patterns across time and space is a central challenge in ecology. Taylor's law of fluctuation scaling, which states that the variance of a population's size or density is proportional to a positive power of the mean size or density, has been widely observed in population dynamics and characterizes variability in multiple scientific domains. However, it is unclear if this phenomenon accurately describes ecological patterns across many orders of magnitude in time, and therefore links otherwise disparate observations. Here, we use water clarity observations from 10,531 days of high‐frequency measurements in 35 globally distributed lakes, and lower‐frequency measurements over multiple decades from 6342 lakes to test this unknown. We focus on water clarity as an integrative ecological characteristic that responds to both biotic and abiotic drivers. We provide the first documentation that variations in ecological measurements across diverse sites and temporal scales exhibit variance patterns consistent with Taylor's law, and that model coefficients increase in a predictable yet non‐linear manner with decreasing observation frequency. This discovery effectively links high‐frequency sensor network observations with long‐term historical monitoring records, thereby affording new opportunities to understand and predict ecological dynamics on time scales from days to decades.

Zooplankton densities reduced by increases in resource N:P in hypereutrophic mesocosms - Patrick T. Kelly; Jason M. Taylor; Isabelle M. Andersen; J. Thad Scott (Hydrobiologia, 2024)

Tropical root responses to global changes: A synthesis - Daniela Yaffar; Laynara F. Lugli; Michelle Y. Wong; Richard J. Norby; Shalom D. Addo‐Danso; Marie Arnaud; Amanda L. Cordeiro; Lee H. Dietterich; Milton H. Diaz‐Toribio; Ming Y. Lee; Om Prakash Ghimire; Chris M. Smith‐Martin; et al. (Global Change Biology, 2024)
Tropical ecosystems face escalating global change. These shifts can disrupt tropical forests' carbon (C) balance and impact root dynamics. Since roots perform essential functions such as resource acquisition and tissue protection, root responses can inform about the strategies and vulnerabilities of ecosystems facing present and future global changes. However, root trait dynamics are poorly understood, especially in tropical ecosystems. We analyzed existing research on tropical root responses to key global change drivers: warming, drought, flooding, cyclones, nitrogen (N) deposition, elevated (e) CO 2 , and fires. Based on tree species‐ and community‐level literature, we obtained 266 root trait observations from 93 studies across 24 tropical countries. We found differences in the proportion of root responsiveness to global change among different global change drivers but not among root categories. In particular, we observed that tropical root systems responded to warming and eCO 2 by increasing root biomass in species‐scale studies. Drought increased the root: shoot ratio with no change in root biomass, indicating a decline in aboveground biomass. Despite N deposition being the most studied global change driver, it had some of the most variable effects on root characteristics, with few predictable responses. Episodic disturbances such as cyclones, fires, and flooding consistently resulted in a change in root trait expressions, with cyclones and fires increasing root production, potentially due to shifts in plant community and nutrient inputs, while flooding changed plant regulatory metabolisms due to low oxygen conditions. The data available to date clearly show that tropical forest root characteristics and dynamics are responding to global change, although in ways that are not always predictable. This synthesis indicates the need for replicated studies across root characteristics at species and community scales under different global change factors.

Fine roots stimulate nutrient release during early stages of leaf litter decomposition in a Central Amazon rainforest - Nathielly P. Martins; Lucia Fuchslueger; Katrin Fleischer; Kelly M. Andersen; Rafael L. Assis; Fabricio B. Baccaro; Plínio B. Camargo; Amanda L. Cordeiro; Adriana Grandis; Iain P. Hartley; Florian Hofhansl; Laynara F. Lugli; et al. (Plant and Soil, 2021)
Purpose Large parts of the Amazon rainforest grow on weathered soils depleted in phosphorus and rock-derived cations. We tested the hypothesis that in this ecosystem, fine roots stimulate decomposition and nutrient release from leaf litter biochemically by releasing enzymes, and by exuding labile carbon stimulating microbial decomposers. Methods We monitored leaf litter decomposition in a Central Amazon tropical rainforest, where fine roots were either present or excluded, over 188 days and added labile carbon substrates (glucose and citric acid) in a fully factorial design. We tracked litter mass loss, remaining carbon, nitrogen, phosphorus and cation concentrations, extracellular enzyme activity and microbial carbon and nutrient concentrations. Results Fine root presence did not affect litter mass loss but significantly increased the loss of phosphorus and cations from leaf litter. In the presence of fine roots, acid phosphatase activity was 43.2% higher, while neither microbial stoichiometry, nor extracellular enzyme activities targeting carbon- and nitrogen-containing compounds changed. Glucose additions increased phosphorus loss from litter when fine roots were present, and enhanced phosphatase activity in root exclusions. Citric acid additions reduced litter mass loss, microbial biomass nitrogen and phosphorus, regardless of fine root presence or exclusion. Conclusions We conclude that plant roots release significant amounts of acid phosphatases into the litter layer and mobilize phosphorus without affecting litter mass loss. Our results further indicate that added labile carbon inputs ( i.e . glucose) can stimulate acid phosphatase production by microbial decomposers, highlighting the potential importance of plant-microbial feedbacks in tropical forest ecosystems.

Highest primary production achieved at high nitrogen levels despite strong stoichiometric imbalances with phosphorus in hypereutrophic experimental systems - Patrick T. Kelly; Jason M. Taylor; Isabelle M. Andersen; Jasmine Stovall; J. Thad Scott (Limnology and Oceanography, 2021)
Lakes in human‐dominated landscapes often face high loads of nutrients that may alter ecosystem function. High N loads relative to P are especially common in agricultural watersheds, where nitrate (NO 3 ) in particular is elevated due to fertilizer application and runoff. While past research has focused extensively on the impact of nutrient loads on reductions in water quality, we still lack assessment of the impact of high N loading and extreme stoichiometric imbalance on ecosystem process rates, specifically measurements of gross primary production (GPP), ecosystem respiration (ER), and net ecosystem productivity (NEP). We used open‐bottomed experimental mesocosms (limnocorrals) to establish four treatments of increasing N : P by increasing N loads while leaving P loads consistent, and measured chlorophyll concentration and metabolic rates. We observed significant differences in productivity among treatments, with higher biomass and GPP in the highest two N : P treatments and a unimodal pattern between GPP and N concentrations. Declines in GPP at high N may have been due to limitation by P or light. In contrast to other studies, we did not observe any significant differences in ER with fertilization, potentially from a lack of dissolved organic carbon loading often associated with higher nutrient concentrations in those lakes. Maximum GPP and NEP observed here was far above commonly cited thresholds for likely P limitation at a molar N : P of approximately 330. Our results highlight the potential for high productivity despite stoichiometric imbalance that is common in agricultural systems, suggesting N management may be important in reducing primary production in hypereutrophic lakes.

Full lifetime perspectives on the costs and benefits of lay‐date variation in tree swallows - David W. Winkler; Kelly K. Hallinger; Teresa M. Pegan; Conor C. Taff; Mo A. Verhoeven; David Chang van Oordt; Maria Stager; Jennifer J. Uehling; Maren N. Vitousek; Michael J. Andersen; Daniel R. Ardia; Amos Belmaker; et al. (Ecology, 2020)
Animals must balance various costs and benefits when deciding when to breed. The costs and benefits of breeding at different times have received much attention, but most studies have been limited to investigating short‐term season‐to‐season fitness effects. However, breeding early, versus late, in a season may influence lifetime fitness over many years, trading off in complex ways across the breeder’s lifespan. In this study, we examined the complete life histories of 867 female tree swallows ( Tachycineta bicolor ) breeding in Ithaca, New York, between 2002 and 2016. Earlier breeders outperformed later breeders in short‐term measures of reproductive output and offspring quality. Though there were weak indications that females paid long‐term future survival costs for breeding early, lifetime fledgling output was markedly higher overall in early‐breeding birds. Importantly, older females breeding later in the season did not experience compensating life history advantages that suggested an alternative equal‐fitness breeding strategy. Rather, most or all of the swallows appear to be breeding as early as they can, and differences in lay dates appear to be determined primarily by differences in individual quality or condition. Lay date had a significant repeatability across breeding attempts by the same female, and the first lay date of females fledged in our population was strongly influenced by the first lay date of their mothers, indicating the potential for ongoing selection on lay date. By examining performance over the entire lifespan of a large number of individuals, we were able to clarify the relationship between timing of breeding and fitness and gain new insight into the sources of variability in this important life history trait.

Multiple phosphorus acquisition strategies adopted by fine roots in low-fertility soils in Central Amazonia - Laynara F. Lugli; Kelly M. Andersen; Luiz E. O. C. Aragão; Amanda L. Cordeiro; Hellen F. V. Cunha; Lucia Fuchslueger; Patrick Meir; Lina M. Mercado; Erick Oblitas; Carlos A. Quesada; Jessica S. Rosa; Karst J. Schaap; et al. (Plant and Soil, 2020)

Correction to: Consequences of the physical nature of the parent material for pedogenesis, nutrient availability, and succession in temperate rainforests - Benjamin L. Turner; Andrew Wells; Kelly M. Andersen; Leo M. Condron (Plant and Soil, 2018)

Consequences of the physical nature of the parent material for pedogenesis, nutrient availability, and succession in temperate rainforests - Benjamin L. Turner; Andrew Wells; Kelly M. Andersen; Leo M. Condron (Plant and Soil, 2018)

Plasticity in nitrogen uptake among plant species with contrasting nutrient acquisition strategies in a tropical forest - Kelly M. Andersen; Jordan R. Mayor; Benjamin L. Turner (Ecology, 2017)
Nitrogen (N) availability influences the productivity and distribution of plants in tropical montane forests. Strategies to acquire soil N, such as direct uptake of organic compounds or associations with root symbionts to enhance N acquisition in exchange for carbon (C), may facilitate plant species coexistence and ecosystem N retention. Alternatively, rapid microbial turnover of soil N forms in tropical soils might promote flexible plant N‐uptake strategies and mediate species coexistence. We tested whether sympatric plant species with different root symbiont associations, and therefore potentially different nutrient acquisition strategies, partition chemical forms of N or show plasticity in N uptake in a tropical pre‐montane forest in Panama. We traced the movement of three 15 N forms into soil pools, microbes, and seedlings of eleven species differing in root traits. Seedlings were grown in a split‐plot field transplant experiment, with plots receiving equimolar mixtures of ammonium, nitrate, and glycine, with one form isotopically labeled in each block. After 48 h, more 15 N was recovered in microbes than in plants, while all pools (extractable organic and inorganic N, microbial biomass, and leaves) contained greater amounts of 15 N from nitrate than from ammonium or glycine. Furthermore, 13 C from dual‐labeled glycine was not recovered in the leaves of any seedling, suggesting the studied species do not directly take up organic N or transform organic N prior to translocation to leaves. Nitrogen uptake differed by root symbiont group only for nitrate, with greater 15 N recovery in plants with arbuscular mycorrhizal (AM) associations or proteoid roots compared to orchids. Some root trait groups differed in 15 N recovery among N forms, with greater nitrate uptake than ammonium or glycine by AM‐associated and N 2 ‐fixing plants. However, only five of eleven species showed differences in uptake among N forms. These results indicate flexibility in uptake of N forms in tropical plants across root trait groups, with only a few species displaying weak preferences for a specific N form.

River–groundwater connectivity in a karst system, Wellington, New South Wales, Australia - Mohammadreza Keshavarzi; Andy Baker; Bryce F. J. Kelly; Martin S. Andersen (Hydrogeology Journal, 2017)

Seedling performance trade‐offs influencing habitat filtering along a soil nutrient gradient in a tropical forest - Kelly M. Andersen; Benjamin L. Turner; James W. Dalling (Ecology, 2014)
Recent studies have provided evidence that trade‐offs in biomass allocation, resource‐use efficiency, and anti‐herbivore defense influence seedling performance and distribution across soil types. Our previous research suggested that soil nutrient availability acted as a filter for understory palm community assembly and species coexistence in a lower montane forest in western Panama. Here, we experimentally tested three potential mechanisms that could be driving this filtering of palm communities along a soil nutrient gradient. We examined seedling performance of 13 understory palm taxa with differing distribution patterns transplanted to five sites, where they were both exposed to and protected from herbivores. We found the strongest evidence for habitat filtering at the lowest‐nutrient site, where seedlings of locally occurring species had significant performance advantages over those of locally absent species, regardless of protection from herbivores. When transplanted to the lowest‐nutrient site, seedlings of naturally occurring species maintained high above‐ to belowground biomass ratios, maximized photosynthetic nitrogen‐use efficiency, and minimized leaf area loss to herbivores and pathogens. Species from low‐fertility sites were therefore able to maintain higher survival and relative growth rates (RGR) at the lowest‐nutrient site than species from more fertile sites. Similar patterns were found for a high‐nutrient site, where naturally occurring species had higher RGR compared to species from lower‐fertility sites. However, the functional traits associated with the differences in performance at high‐nutrient sites were less clear, perhaps due to increased light limitation in the understory of these sites. At higher‐nutrient sites, protection from herbivores significantly reduced leaf area damage and mortality rates in seedlings, particularly for naturally occurring species. Overall, morphological and physiological traits were more strongly coupled with soil nutrient availability than were leaf damage or seedling performance across the sites. Nonetheless, the coordination of all three trade‐offs was related to the strongest performance advantage and, therefore, ecological filtering along the soil nutrient gradient in this lower montane forest.

A reassessment of the Lower Namoi Catchment aquifer architecture and hydraulic connectivity with reference to climate drivers - B. F. J. Kelly; W. Timms; T. J. Ralph; B. M. S. Giambastiani; A. Comunian; A. M. McCallum; M. S. Andersen; R. S. Blakers; R. I. Acworth; A. Baker (Australian Journal of Earth Sciences, 2014)

Antiretroviral drugs induce oxidative stress and neuronal damage in the central nervous system - Cagla Akay; Michael Cooper; Akinleye Odeleye; Brigid K. Jensen; Michael G. White; Fair Vassoler; Patrick J. Gannon; Joseph Mankowski; Jamie L. Dorsey; Alison M. Buch; Stephanie A. Cross; Denise R. Cook; et al. (Journal of NeuroVirology, 2014)
HIV-associated neurocognitive disorder (HAND), characterized by a wide spectrum of behavioral, cognitive, and motor dysfunctions, continues to affect approximately 50 % of HIV(+) patients despite the success of combination antiretroviral drug therapy (cART) in the periphery. Of note, potential toxicity of antiretroviral drugs in the central nervous system (CNS) remains remarkably underexplored and may contribute to the persistence of HAND in the cART era. Previous studies have shown antiretrovirals (ARVs) to be neurotoxic in the peripheral nervous system in vivo and in peripheral neurons in vitro. Alterations in lipid and protein metabolism, mitochondrial damage, and oxidative stress all play a role in peripheral ARV neurotoxicity. We hypothesized that ARVs also induce cellular stresses in the CNS, ultimately leading to neuronal damage and contributing to the changing clinical and pathological picture seen in HIV-positive patients in the cART era. In this report, we show that ARVs are neurotoxic in the CNS in both pigtail macaques and rats in vivo. Furthermore, in vitro, ARVs lead to accumulation of reactive oxygen species (ROS), and ultimately induction of neuronal damage and death. Whereas ARVs alone caused some activation of the endogenous antioxidant response in vitro, augmentation of this response by a fumaric acid ester, monomethyl fumarate (MMF), blocked ARV-induced ROS generation, and neuronal damage/death. These findings implicate oxidative stress as a contributor to the underlying mechanisms of ARV-induced neurotoxicity and will provide an access point for adjunctive therapies to complement ARV therapy and reduce neurotoxicity in this patient population.

Patterns of tree community composition along a coastal dune chronosequence in lowland temperate rain forest in New Zealand - Benjamin L. Turner; Andrew Wells; Kelly M. Andersen; Leo M. Condron (Plant Ecology, 2012)

Understanding groundwater processes by representing aquifer heterogeneity in the Maules Creek Catchment, Namoi Valley (New South Wales, Australia) - B. M. S. Giambastiani; A. M. McCallum; M. S. Andersen; B. F. J. Kelly; R. I. Acworth (Hydrogeology Journal, 2012)

Trait-based community assembly of understory palms along a soil nutrient gradient in a lower montane tropical forest - Kelly M. Andersen; Maria Jose Endara; Benjamin L. Turner; James W. Dalling (Oecologia, 2012)

Soil‐based habitat partitioning in understorey palms in lower montane tropical forests - Kelly M. Andersen; Benjamin L. Turner; James W. Dalling (Journal of Biogeography, 2010)
Aim Dispersal assembly and niche assembly are two competing theories proposed to explain the maintenance of species diversity in tropical forests. Dispersal theory emphasizes the role of chance colonization events and distance‐limited seed dispersal in explaining species abundance and distribution, whereas niche theory emphasizes differences among species in requirements for potentially limiting resources. Species distribution patterns in tropical forests often correlate with geology and topography, but tests of the relative importance of dispersal and niche partitioning have been hampered by an inadequate characterization of resource availability. The aim of this study was to explore how soil chemical and physical properties, climate, and geographic distance affect understorey palm communities in lower montane forests. Location Fortuna Forest Reserve, Chiriqui Province, and Palo Seco Forest Reserve, Bocas del Toro Province, in western Panama. Methods Understorey palms and soil nutrient concentrations were surveyed within 10 sites on different soil types across a 13‐km transect. Variation in palm community composition was examined in relation to spatial and environmental variables. Results The 25 understorey palm species recorded in the study were non‐randomly distributed among forests differing in soil nutrient availability. In support of dispersal theory, floristic similarity decreased predictably with increasing geographic distance. However, environmental and soil variables were also correlated with geographic distance. Floristic similarity was also highly associated with a subset of environmental variables. Variation in palm community similarity was most strongly correlated with inorganic nitrogen availability and cation concentration. A subset of soil variables had a stronger relationship with floristic similarity when geographic distance was controlled for than did geographic distance when differences in soils were controlled for. Main conclusions Both dispersal and niche processes affect palm species distribution patterns. Although spatially limited dispersal may influence species distribution patterns, soil‐based habitat associations, particularly with respect to soil nitrogen, cation availability and aluminium concentrations, remain important factors influencing palm community composition at the mesoscale level in this tropical montane forest.

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Arbuscular mycorrhizal communities in tropical forests are affected by host tree species and environment - Catherine E. Lovelock; Kelly Andersen; Joseph B. Morton (Oecologia, 2003)